Electrolyte Disturbance among Hypertensive Patient In Baquba teaching hospital , Diyala , Iraq - Jaafar, Ali M; Jaafar, Ali M; Ali, Mohaimen A (International Journal of Psychosocial Rehabilitation, 2020)
T Hypertension attack about ¼ of adult’s people all over the world, this attack come from the internal and external surrounding environment. Electrolyte imbalances are common findings in many diseases Sodium, potassium, calcium, and other ions should be balanced and any change in ions value must take inconsideration as a colligative and associated style, any investigation have to stress of understanding of clinical scenario searching on successful and effective therapy. In this study we took these electrolyte and study their disturbance in the hypertensive patient and connect it to other disorders like diabetes and IHD. A case – control study was done in Ba’quba Teaching hospital , Diyala , Iraq during the period of 16th of septemper 2018 – 3rd of January 2019 on one hundred primary person were included in our study , Eighty one were the cases who have hypertension ( 55 female and 25 male ) compared to a twenty healthy person” Control” ( 11 female and 10 male ) which the take information by questionnaire then aspirate blood and send for investigation (Na, Cl , K , Ca , Phosphorus , B.Urea , S.Creatinine , RBS And HBA1c ) Then classify them into three groups : first who had hypertension and IHD only , second who had Hypertension and Diabetes and third group who had Hypertension , Diabetes and IHD . The result of our study demonstrate that the first group had a significant reduce in serum magnesium and increase of serum NaCl , the second group demonstrate that there is significant reducing in serum Mg++ , Ca++ and K+ and increase in serum Nacl , third group demonstrates significant reducing of serum Mg++.. In this study we demonstrate a significant reduction in both serum magnesium and calcium levels among patients with hypertension , diabetes, and significant inverse correlation of both serum magnesium and calcium with hypertension ,diabetes and cardiovascular diseases